Study on Optimization of Stope Structural Parameters and Filling Scheme of Wawu Phosphate Mine in Yichang City, China - Peng, Gao; Gaoyi, Dong; Jingsong, Chen; Zhou, Chunmei; Manqing, Lin; Weizhong, Zhang; Yang, Sun (Frontiers in Earth Science, 2022)
Reasonable stope structural parameters are very important to ensure the safety and efficiency of mining. In this paper, based on the elastic-plastic constitutive model of Mohr-Coulomb strength criterion, the reasonable span and critical span are calculated by using simply supported beam theory and mine room width calculation formula. PLAXIS2D finite element analysis software was used to conduct numerical simulation research on 7 m × 9 m, 5 m × 12 m stope structure parameter schemes and 7 m × 9m, 5 m × 12 m waste rock filling schemes. The optimal structure parameters of the stope were determined based on the calculation and analysis of displacement variation rule, surrounding rock stress distribution and plastic zone. The analysis and simulation results show that Case 1 one-time mining 7 m × 9 m and Case 3 one-time mining 5 m × 12 m, the plastic zone is connected, the simulation calculation is not convergent, and the stope is unstable. Case 2 waste rock filling 7 m × 9 m and Case 4 waste rock filling 5 m × 12 m, the distribution and change of stress, displacement and plastic zone in the goaf under the two cases are compared, and finally the waste rock filling 7 m × 9 m is obtained can improve the economy and safety of mining in the mining area, and verify the feasibility of implementing stope structural parameters and waste rock filling mining system is verified.